Vibration and acoustic emission monitoring the stability of peakless tool turning: Experiment and modeling; Journal of Materials Processing Technology; Vol. 246 - Filippov A. V. Andrey Vladimirovich; Nikonov A. Yu. Anton Yurjevich; Rubtsov V. E. Valery Evgenjevich; Dmitriev A. E. Andrey Ivanovich; Tarasov S. Yu. Sergei Yulievich (2017, 2017)
Title screen